Contribution of Micro-Finance on Socio-Economic Development of Rural Community - Dhakal, Chandra Prasad; Nepal, Govinda (Journal of Advanced Academic Research, 2017)
Microfinance institutions are established to promote the financial activities mainly saving and credit in community. Microfinance’s activities are focused on reducing poverty level of community people. Poor, disadvantaged, marginalize and women are in mainstream of microfinance’s programs. The study was focused on finding out the contribution of microfinance on socio-economic development of rural community. The study was based on the quantitative design. Cross-sectional data was collected from the 8 microfinances of Syangja district. Purposive sampling technique was adopted to select the respondents. The perceptual analysis of data reported the significant contribution of micro-finance in social change and development. Microfinances working since 2 to 20 years covering the diverse field of social activities were the samples of the study. There was a need to improve the internal management of microfinance to provide the services more effectively.